Measures of the winter package EC and biogas power plants in Croatia - Ivanović, Milan, ekonomist (Array, 2018)
This paper is based on the revised EU energy policy measures proposed by the European Commission in the so-called Winter Package, with special reference to biogas plants in the Republic of Croatia. The paper gives an overview of biogas power plants built in Croatia, a technological framework for their functioning, the installed power and their contribution to power supply in the country. The paper points to the importance of electricity and heat production from biogas power plants and the possibilities of a framework for the future development of these power plants in the Republic of Croatia.